Volatiles from three genome sequenced fungi from the genus Aspergillus - Dickschat, Jeroen S.; Celik, Ersin; Brock, Nelson L. (Beilstein Journal of Organic Chemistry, 2018)
The volatiles emitted by agar plate cultures of three genome sequenced fungal strains from the genus Aspergillus were analysed by GC–MS. All three strains produced terpenes for which a biosynthetic relationship is discussed. The obtained data were also correlated to genetic information about the encoded terpene synthases for each strain. Besides terpenes, a series of aromatic compounds and volatiles derived from fatty acid and branched amino acid metabolism were identified. Some of these compounds have not been described as fungal metabolites before. For the compound ethyl (E)-hept-4-enoate known from cantaloupe a structural revision to the Z stereoisomer is proposed. Ethyl (Z)-hept-4-enoate also occurs in Aspergillus clavatus and was identified by synthesis of an authentic standard.
Keywords: Aspergillus; GC–MS; genomics; terpenes; volatiles

(untitled) - Moore, R. N.; Bigam, G.; Chan, J. K.; Hogg, A. M.; Nakashima, T. T.; Vederas, J. C. (J. Am. Chem. Soc., 1985)

(untitled) - Hamed, R. B.; Gomez-Castellanos, J. R.; Henry, L.; Ducho, C.; McDonough, M. A.; Schofield, C. J. (Nat. Prod. Rep., 2013)

(untitled) - Minto, R. E.; Townsend, C. (Chem. Rev., 1997)

(untitled) - Hallen, H. E.; Luo, H.; Scott-Craig, J. S.; Walton, J. D. (Proc. Natl. Acad. Sci. U. S. A., 2007)

(untitled) - Dickschat, J. S. (Nat. Prod. Rep., 2017)

(untitled) - Lemfack, M. C.; Gohlke, B.-O.; Toguem, S. M. T.; Preissner, S.; Piechulla, B.; Preissner, R. (Nucleic Acids Res., 2018)

(untitled) - Zawirksa-Wojtasiak, R. (Food Chem., 2004)

(untitled) - Simon, A.; Dunlop, R. W.; Ghisalberti, E. L.; Sivasithamparam, K. (Soil Biol. Biochem., 1988)

(untitled) - Worasatit, N.; Sivasithamparam, K.; Ghisalberti, E. L.; Rowland, C. (Mycol. Res., 1994)

(untitled) - Chitarra, C. S.; Abee, T.; Rombouts, F. M.; Posthumus, M. A.; Dijksterhuis, J. (Appl. Environ. Microbiol., 2004)

(untitled) - Fäldt, J.; Jonsell, M.; Nordlander, G.; Borg-Karlson, A.-K. (J. Chem. Ecol., 1999)

(untitled) - Stadler, M.; Læssøe, T.; Fournier, J.; Decock, C.; Schmieschek, B.; Tichy, H.-V.; Peršoh, D. (Stud. Mycol., 2014)

(untitled) - Zamir, L. O.; Gauthier, M. J.; Devor, K. A.; Nadeau, Y.; Sauriol, F. (J. Chem. Soc., Chem. Commun., 1989)

(untitled) - Vadlapudi, V.; Borah, N.; Yellusani, K. R.; Gade, S.; Reddy, P.; Rajamanikyam, M.; Vempati, L. N. S.; Gubbala, S. P.; Chopra, P.; Upadhyayula, S. M.; Amanchy, R. (Sci. Rep., 2017)

(untitled) - Kaminski, E.; Stawicki, S.; Wasowizc, E. (Appl. Microbiol., 1974)

(untitled) - Seifert, R. M.; King, A. D., Jr (J. Agric. Food Chem., 1982)

(untitled) - Ito, K.; Yoshida, K.; Ishikawa, T.; Kobayashi, S. (J. Ferment. Bioeng., 1990)

(untitled) - Sunesson, A.-L.; Vaes, W. H. J.; Nilsson, C.-A.; Blomquist, G.; Andersson, B.; Carlson, R. (Appl. Environ. Microbiol., 1995)

(untitled) - Jeleń, H. H.; Grabarkiewicz-Szczesna, J. (J. Agric. Food Chem., 2005)

(untitled) - Roze, L. V.; Chanda, A.; Laivenieks, M.; Beaudry, R. M.; Artymovich, K. A.; Koptina, A. V.; Awad, D. W.; Valeeva, D.; Jones, A. D.; Linz, J. E. (BMC Biochem., 2010)

(untitled) - Takeuchi, T.; Kimura, T.; Tanaka, H.; Kaneko, S.; Ichii, S.; Kiuchi, M.; Suzuki, T. (Surf. Interface Anal., 2012)

(untitled) - Heddergott, C.; Calvo, A. M.; Latgé, J. P. (Eukaryotic Cell, 2014)

(untitled) - Grob, K.; Zürcher, F. (J. Chromatogr., 1976)

(untitled) - Matsui, K.; Sasahara, S.; Akakabe, Y.; Kajiwara, T. (Biosci., Biotechnol., Biochem., 2003)

(untitled) - Kuribayashi, T.; Kaise, H.; Uno, C.; Hara, T.; Hayakawa, T.; Joh, T. (J. Agric. Food Chem., 2002)

(untitled) - Assaf, S.; Hadar, Y.; Dosoretz, C. G. (J. Agric. Food Chem., 1995)

Identification of Essential Oil Components by Gas Chromatography/Mass Spectrometry - Adams, R. P. (Allured, 2009)

(untitled) - Citron, C. A.; Gleitzmann, J.; Laurenzano, G.; Pukall, R.; Dickschat, J. S. (ChemBioChem, 2012)

(untitled) - Dickschat, J. S.; Bode, H. B.; Mahmud, T.; Müller, R.; Schulz, S. (J. Org. Chem., 2005)

(untitled) - Nawrath, T.; Dickschat, J. S.; Müller, R.; Jiang, J.; Cane, D. E.; Schulz, S. (J. Am. Chem. Soc., 2008)

(untitled) - Jiang, J.; He, X.; Cane, D. E. (Nat. Chem. Biol., 2007)

(untitled) - Peters, R. J. (Nat. Prod. Rep., 2010)

(untitled) - Tudzynski, B.; Kawaide, H.; Kamiya, Y. (Curr. Genet., 1998)

(untitled) - Dickschat, J. S.; Brock, N. L.; Citron, C. A.; Tudzynski, B. (ChemBioChem, 2011)

(untitled) - Hong, Y. J.; Tantillo, D. J. (Org. Lett., 2006)

(untitled) - Cane, D. E.; Ha, H. J. (J. Am. Chem. Soc., 1986)

(untitled) - Brock, N. L.; Huss, K.; Tudzynski, B.; Dickschat, J. S. (ChemBioChem, 2013)

(untitled) - Faraldos, J. A.; Wu, S.; Chappell, J.; Coates, R. M. (Tetrahedron, 2007)

(untitled) - Priegnitz, B.-E.; Brandt, U.; Pahirulzaman, K. A. K.; Dickschat, J. S.; Fleißner, A. (Eukaryotic Cell, 2015)

(untitled) - Niehaus, E.-M.; Schumacher, J.; Burkhardt, I.; Rabe, P.; Münsterkötter, M.; Güldener, U.; Sieber, C. M. K.; Dickschat, J. S.; Tudzynski, B. (Front. Microbiol., 2017)

(untitled) - Siegmund, B.; Derler, K.; Pfannhauser, W. (J. Agric. Food Chem., 2001)

(untitled) - Fan, W.; Qian, M. C. (J. Agric. Food Chem., 2006)

(untitled) - Park, Y.-C.; San, K.-Y.; Bennett, G. N. (Appl. Microbiol. Biotechnol., 2007)

(untitled) - Beaulieu, J. C.; Lancaster, V. A. (J. Agric. Food Chem., 2007)

(untitled) - Schalchli, H.; Hormazabal, E.; Becerra, J.; Birkett, M.; Alvear, M.; Vidal, J.; Quiroz, A. (Chem. Ecol., 2011)

(untitled) - Schmidberger, P. C.; Schieberle, P. (J. Agric. Food Chem., 2017)

(untitled) - Suwannarach, N.; Kumla, J.; Bussaban, B.; Nuangmek, W.; Matsui, K.; Lumyong, S. (Crop Prot., 2013)

(untitled) - Barra, L.; Barac, P.; König, G. M.; Crüsemann, M.; Dickschat, J. S. (Org. Biomol. Chem., 2017)